2003
DOI: 10.1271/bbb.67.2055
|View full text |Cite
|
Sign up to set email alerts
|

350-kDa Royal Jelly Glycoprotein (Apisin), Which Stimulates Proliferation of Human Monocytes, Bears the β1-3GalactosylatedN-Glycan: Analysis of theN-Glycosylation Site

Abstract: While doing a structural analysis of minor component N-glycans linked to 350-kDa royal jelly glycoprotein (RJGP), which stimulates the proliferation of human monocytes, we found that a Galbeta1-3GlcNAcbeta1-4Man unit occurs on the insect glycoprotein. The structure of the fluorescence-labeled N-glycan was analyzed by sugar component analysis, IS-MS, and (1)H-NMR. The structural analysis showed that the 350-kDa RJGP bears Galbeta1-3GlcNAcbeta1-4(GlcNAcbeta1-2)Manalpha1-3 (Manalpha1-3Manalpha1-6)Manbeta1-4GlcNAc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 13 publications
2
61
0
1
Order By: Relevance
“…4 A/G, albumin to globulin ratio; GOT, glutamic-oxaloacetic transaminase; GPT, glutamic-pyruvic transaminase; ␥-GTP, ␥-glutamyl transpeptidase. …”
Section: Subject Characteristics and Blood Biochemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 A/G, albumin to globulin ratio; GOT, glutamic-oxaloacetic transaminase; GPT, glutamic-pyruvic transaminase; ␥-GTP, ␥-glutamyl transpeptidase. …”
Section: Subject Characteristics and Blood Biochemical Analysesmentioning
confidence: 99%
“…RJ contains a mix of proteins (12-15%), sugars (10-16%), lipids (3-6%), free amino acids, vitamins, minerals, and fatty acids. Several researchers have found that RJ has anti-tumor ( 1 ), anti-inflammatory ( 2 ), antioxidant ( 3 ), and cell proliferative activities ( 4 ). RJ reduces total cholesterol levels in experimental animals ( 5 ) and atherosclerosis in humans ( 6 ).…”
mentioning
confidence: 99%
“…Royalisin is an antimicrobial peptide against Gram-positive bacteria and fungi [24,25], the Jelleines are an antimicrobial family of peptides against Gram-positive, Gram-negative bacteria and yeasts [26]. Apismin is a 54 amino acid peptide highly expressed in the head of the honey-bee and is able to strongly bind apalbumin 1 [27] and apisin is a 350 kDa glycoprotein that stimulates the proliferation of human monocytes [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…RJ extract or RJ proteins used as cell growth factors or as an alternative to FBS have been paid more attention to in cell culture (Watanabe et al, 1996;Kamakura et al, 2001). The evaluation of RJ extract or RJ proteins was implemented in several cell lines from insects, rats, and humans (Kimura Y. et al, 1996;Kimura M. et al, 2003;Salazar-Olivo and PazGonzalez, 2005). However, most previous work (Musa et al, 2013;Yu et al, 2015) focused on using single RJ extract or RJ proteins to replace FBS.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, more investigations to evaluate the activities of RJ or RJ proteins have been carried out (Karaca et al, 2012;Musa et al, 2013). Kimura et al (2003) found that 350-kDa RJ glycoprotein stimulates proliferation of human monocytes. Kimura et al (1996) found that 55-kDa RJ glycoportein (RJGP) maintains the high viability of the rat liver primary cultured cell and is a different molecular species from 350-kDa RJGP.…”
Section: Introductionmentioning
confidence: 99%